The Ketogenic Effect of Medium-Chain Triacylglycerides - Lin, Ting-Yu; Liu, Hung-Wen; Hung, Tsung-Min (Frontiers in Nutrition, 2021)
Medium-chain triacylglycerides (MCTs) are dietary supplements that can induce ketosis without the need for a traditional ketogenic diet or prolonged fasting. They have the potential to marginally delay the progression of neurodegenerative diseases, such as Alzheimer’s disease. However, there have been inconsistencies in reports of the MCT dose–response relationship, which may be due to differences in MCT composition, participant characteristics, and other factors that can influence ketone generation. To resolve these discrepancies, we reviewed studies that investigated the ketogenic effect of MCTs in healthy adults. Aside from the treatment dose, other factors that can influence the ketogenic response, such as accompanying meals, fasting duration, and caffeine intake, were assessed. Based on the available literature, four practical recommendations are made to optimize the ketogenic effect of MCTs and reduce unwanted side effects (primarily gastrointestinal discomfort and diarrhea). First, the starting dose should be either 5 g of octanoic acid (caprylic acid [C8]; a component of MCTs) or 5 g of a combination of C8 and decanoic or capric acid (C10; another component of MCTs), and the dose should be progressively increased to 15–20 g of C8. Second, MCTs should be consumed after an overnight fast, without an accompanying meal if tolerable, or with a low-carbohydrate meal. Third, the addition of caffeine may slightly increase the ketogenic response. Fourth, emulsifying the MCTs might increase their ketogenic effect and alleviate side effects.